Paddy Field Water Movement Through Soil Profiles Under Different Water Management Practices: A HYDRUS 1D Model Study (Bangladesh Rice Journal, 2023)
Physical measurement of hydrological processes through soil profile is very complicated and timeconsuming. Complex and coupled physical processes like water movement with soil matric potential in puddled paddy field can be simulated using physical process-based model HYDRUS 1D. The model simulation was setup for the multilayered (different soil materials at 0-15 and 15-30 cm depth) paddy fields having continuous flooded irrigation (CFI) practice and water saving Alternate Wetting and Drying (AWD) practice. Measured soil physical properties of three Bangladesh Rice Research Institute (BRRI) regional station farms (Kushtia, Sirajganj, and Rangpur) were used as model input, initial and boundary conditions configuration. The model was calibrated and validated using the water data of a dry season field experiment in Kushtia. The calibrated (RMSE of 0.54 cm, d of 0.94, NSE of 0.89) water level data validated successfully with observed water level data of AWD practiced paddy field (d of 0.95, NSE of 0.92). Soil water content reached the threshold/critical level in AWD practice (-101 cm of water soil matric potential at 15 cm soil depth) earlier in light textured soil (loam or sandy loam) compared to heavy textured soil (clay). The physical properties of the layered soils (i.e., soil particle size distribution and soil water release curve, SWRC) did not affect much on water movement in CFI practice, but it had substantial impact on field water movement under AWD practice. The change in soil water storage followed the general trend for respective soil water holding and releasing capacity, clay soil was heavier and released water slowly than that of loam or sandy loam soils. The positive water flux above 15 cm of soil profile mainly drove the water flow due to evapotranspiration and soil water and pressure distribution along the soil profile while the negative fluxes below 15 cm of soil depth due to infiltration or percolation contributed as a secondary force. A basic understanding of HYDRUS simulated results would lead to realize the total physiohydrological environment in the paddy field.Bangladesh Rice J. 25 (2) : 57-67, 2021